Analisis Kesulitan Belajar Siswa Dalam Proses Pembelajaran Komputer dan Jaringan Dasar Pada Kelas XI SMKN 1 Ranah Ampek Hulu Tapan - Zari, Dhantik Fermata; Alfiriani, Adlia; Nurdin, Bernediv (Universitas Labuhanbatu, 2023)
This research aims to determine the level of student learning difficulties in learning computers and basic networks in class Xl at SMKN 1 Ranah Ampek Hulu Tapan for the 2023/2024 academic year. This research is descriptive using a quantitative approach using a questionnaire. The population in this study was class Xl students at SMKN 1 Ranah Ampek Hulu Tapan using a saturated sampling technique. The results of this research show that the learning difficulties of class, 5) Family skills at 72%, 6) Community skills at 75%. The results showed that class Xl students at SMKN 1 Ranah Ampek Hulu Tapan. The 2023/2024 school year has a level of student learning difficulty in the